2010
DOI: 10.1039/b9pp00145j
|View full text |Cite
|
Sign up to set email alerts
|

In vitro tools for photobiological testing: molecular responses to simulated solar UV of keratinocytes growing as monolayers or as part of reconstructed skin

Abstract: Epidermal keratinocytes are critical targets for UV-induced genotoxicity as their transformation by sunlight overexposure can lead to skin cancer such as basal cell carcinoma (BCC) and squamous cell carcinoma (SCC). Therefore, assessment of photoprotection should involve early markers associated with DNA photodamage. Here, the same normal human keratinocytes either in monoculture (KC) or in full thickness reconstructed skin (RS) were compared with respect to their response to simulated solar UV (SSUV) exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…Regarding the role of p53 in DNA repair, increased p53 expression correlates with increased DNA damage, suggesting that the loss of Nrf2 may fail to protect DNA but could enable abundant p53 to repair the DNA damage. Indeed, a previous study showed that the extent of DNA damage correlates with the amount of UV exposure in various skin cells and models [34]. In our study, the higher p53 expression observed in Nrf2 KO mice after UVB exposure could be an indicator of more sustained DNA damage in need of repair.…”
Section: Discussionsupporting
confidence: 58%
“…Regarding the role of p53 in DNA repair, increased p53 expression correlates with increased DNA damage, suggesting that the loss of Nrf2 may fail to protect DNA but could enable abundant p53 to repair the DNA damage. Indeed, a previous study showed that the extent of DNA damage correlates with the amount of UV exposure in various skin cells and models [34]. In our study, the higher p53 expression observed in Nrf2 KO mice after UVB exposure could be an indicator of more sustained DNA damage in need of repair.…”
Section: Discussionsupporting
confidence: 58%
“…After exposing the skin model to DUVR 13 J cm −2 , we examined the modulation of 43 genes involved in different UV‐induced signalling pathways in dermal fibroblasts and epidermal keratinocytes respectively. Genes were considered to be modulated by DUVR when MF was ≥2 or ≤0.5 with a significant P < 0.05 .…”
Section: Resultsmentioning
confidence: 99%
“…The CPD detection assay is an important tool for evaluating genotoxicity in epithelial cells, as these lesions are highly mutagenic and typically induced by UVB radiation (Marrot et al, 2010). After 1 hour of treatment, there is an increase in the amount of CPDs in the carbaryl and solar radiation combined treatment group and, after 6 hours of treatment, there is an equal response between the combined treatment group and the solar radiation group (Figure 4).…”
Section: Resultsmentioning
confidence: 99%